The Effect of Floor and Swiss Ball Exercises Using Circuit Training Methods towards Balance, Strength, Flexibility and Muscle Endurance - Risfandi Setyawan; Hari Setijono; Nining Widyah Kusnanik (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
The purpose of this study was to analyze the effect of floor exercises and swiss ball exercises with the circuit training method on balance, strength, flexibility and muscle endurance. This research uses a quasi-experimental, floor exercise treatment and Swiss ball exercise using the circuit training method with 10 training posts. The population in this study was students of physical education and sports of STKIP PGRI Jombang 2015, with a total population of 80 male students, with an average age of ±19 years, height ± 166.31cm, weight ± 58.63kg. From the test of each group (paired sample) obtained a significant difference between the pretest and posttest on each variable (p-value> 0.05). Meanwhile, from the ANOVA test was found out that there was a difference in the average results of the physical condition of each variable in each exercise method. The study concluded that: 1) there was an effect of floor and swiss ball exercises aided circuit training method, there is a significant enhancement of balance, strength, flexibility and muscle endurance; 2) in conventional training there was also a significant enhancement on balance, strength and flexibility. There was no significant enhancement in abdominal muscle strength, abdominal muscle endurance, and leg muscle endurance; and 3) there were significant differences between the three groups in balance, strength, flexibility and muscle endurance.